Should fathers also do kangaroo care - ÖZEK, EREN; BİLGEN, HÜLYA SELVA (My University, 2022)
Objective The aim of the study is to compare the effect of maternal and paternal Kangaroo care (KC) on vital signs and cerebral oxygen saturation (rSO2) parameters. Methods This randomized study included 35 preterm infants born at 32 weeks gestation or earlier. The body temperature, respiratory rate, heart rate, oxygen saturation (sPO2), and cerebral oxygen saturation (rSO2) were measured at the postnatal 35th week of gestation during three periods: in the incubator before KC, during KC with the mother or father , and in the incubator after KC. The measured parameters of the three periods were compared within each group (mother or father) and between the groups (mother and father). Results There was no statistically significant difference between the vital signs during the three periods, both in the mother and father groups, and between the parents. The rSO2 values increased significantly in both parents ( p <0.001) during and after KC. When we compared parents, rSO2 values were significantly higher during ( p = 0.015) and after ( p = 0.046) mother KC. Conclusion The difference between M-KC and F-KC can be ignored as the cerebral near infra-red spectroscopy values are within normal limits. The active participation of fathers in KC should be encouraged by health professionals in all NICUs.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Cerrahi Tıp Bilimleri; Kadın Hastalıkları ve Doğum; Medicine; Health Sciences; Internal Medicine Sciences; Child Health and Diseases; Surgery Medicine Sciences; Obstetrics and Gynecology; KADIN HASTALIKLARI & DOĞUM; Klinik Tıp; Klinik Tıp (MED); PEDİATRİ; OBSTETRICS & GYNECOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); PEDIATRICS; Pediatri; Pediatri, Perinatoloji ve Çocuk Sağlığı; Doğum ve Jinekoloji; Pediatrics; Pediatrics, Perinatology and Child Health; kangaroo care; near-infrared spectroscopy; preterm infants; TO-SKIN CONTACT; PRETERM INFANTS; MOTHER CARE; BIRTH; OUTCOMES; STRESS